Internal capacitive compensation of the reactive power of the screw electromechanical converter - Zablodskiy, M. M.; Chuenko, R. M.; Kovalchuk, S. I.; Kruhliak, H. V.; Kovalchuk, O. I. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Introduction. A special category among induction machines with a massive rotor is occupied by the class of multifunctional electromechanical energy converters, which are integrated with the links of technological processes Problem. The exchange of reactive energy between the source and the electromechanical converter during periods of operation with a low load leads to a significant decrease in its efficiency and power factor. With the use of non-linear loads and taking into account possible resonance, it has become more difficult to improve the power factor by installing capacitor banks. Goal. Increasing the energy indicators of the electromechanical converter by spatial displacement of the main and additional stator windings and internal capacitive compensation. Methodology. Comparative analysis of connection schemes and spatial arrangement of stator windings when using internal capacitive compensation. Modeling and experimental studies of electromagnetic and electromechanical characteristics of a screw electromechanical converter. Results. The distribution of electromagnetic quantities was established and the choice of the angle of spatial displacement of the main and additional windings of the stator phases of the modified converter, which ensure an increase in the value of the electromagnetic torque and power factor, was justified. The results of experimental studies of the screw electromechanical converter are presented. Originality. For the first time, a method of internal capacitive compensation of reactive power is proposed for multifunctional electromechanical converters of technological purpose. Practical value. The use of the proposed method of spatial displacement of the main and additional stator windings and internal capacitive compensation will ensure an increase in the energy performance of the screw electromechanical converter.

Вступ. Особливу категорію серед асинхронних машин з масивним ротором займає клас поліфункціональних електромеханічних перетворювачів енергії, які інтегровані з ланками технологічних процесів. Проблема. Обмін реактивною енергією між джерелом і електромеханічним перетворювачем в періоди роботи з низьким навантаженням приводить до суттєвого зниження його ефективності і коефіцієнта потужності. З використанням нелінійних навантажень і урахуванням можливого резонансу покращити коефіцієнт потужності встановленням батарей конденсаторів стало складніше. Мета. Підвищення енергетичних показників шнекового електромеханічного перетворювача шляхом внутрішньої ємнісної компенсації реактивної потужності. Методологія. Порівняльний аналіз схем з'єднання і просторового розташування обмоток статора при застосуванні внутрішньої ємнісної компенсації. Моделювання та експериментальні дослідження електромагнітних і електромеханічних характеристик шнекового електромеханічного перетворювача. Результати. Встановлено розподіл електромагнітних величин і обґрунтовано вибір кута просторового зміщення основної і додаткової обмоток фаз статора модифікованого перетворювача, які забезпечують збільшення електромагнітного моменту та коефіцієнта потужності. Наведено результати експериментальних досліджень шнекового електромеханічного перетворювача. Оригінальність. Вперше для поліфункціональних електромеханічних перетворювачів технологічного призначення запропоновано метод внутрішньої ємнісної компенсації реактивної потужності. Практичне значення. Використання запропонованого методу просторового зміщення основної і додаткової обмоток статора та внутрішньої ємнісної компенсації забезпечить підвищення енергетичних показників шнекового електромеханічного перетворювача.
Внутрішня ємнісна компенсація реактивної потужності шнекового електромеханічного перетворювача
Keywords: Maxwell's equation; multifunctional electromechanical converter; stator winding; finite element method; capacitor capacity; рівняння Максвелла; поліфункціональний електромеханічний перетворювач; обмотка статора; метод скінченних елементів; ємність конденсатора